Disorder of phospholipid metabolism in the renal cortex and medulla contributes to acute tubular necrosis in mice after cantharidin exposure using integrative lipidomics and spatial metabolomics - Tianmu He; Kexin Lin; Lijuan Xiong; Wen Zhang; Huan Zhang; Cancan Duan; Xiaofei Li; Jianyong Zhang (Journal of Pharmaceutical Analysis)
Cantharidin (CTD), a natural compound used to treat multiple tumors in the clinic setting, has been limited due to acute kidney injury (AKI). However, the major cause of AKI and its underlying mechanism remain to be elucidated. Serum creatinine (SCr) and blood urea nitrogen (BUN) were detected through pathological evaluation after CTD (1.5 mg/kg) oral gavage in mice in 3 days. Kidney lipidomics based on ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to investigate lipids disorder after CTD exposure in mice. Then, spatial metabolomics based on matrix-assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI) was used to detect the kidney spatial distribution of lipids. Integrative analysis was performed to reveal the spatial lipid disorder mechanism and verify key lipids in vitro. The results showed that the levels of SCr and BUN were increased, and tubular necrosis was observed in mouse kidneys, resulting in acute tubular necrosis (ATN) in CTD-induced AKI. Then, lipidomics results revealed that after CTD exposure, 232 differential lipid metabolites and 11 pathways including glycerophospholipid (GP) and sphingolipid (SL) metabolism were disrupted. Spatial metabolomics revealed that 55 spatial differential lipid metabolites and nine metabolic pathways were disturbed. Subsequently, integrative analysis found that GP metabolism was stimulated in the renal cortex and medulla, whereas SL metabolism was inhibited in the renal cortex. Up-regulated lysophosphatidylcholine (LysoPC) (18:2(9Z,12Z)), LysoPC (16:0/0:0), glycerophosphocholine, and down-regulated sphingomyelin (SM) (d18:0/16:0), SM (d18:1/24:0), and SM (d42:1) were key differential lipids. Among them, LysoPC (16:0/0:0) was increased in the CTD group at 1.1196 μg/mL, which aggravated CTD-induced ATN in human kidney-2 (HK-2) cells. LysoPC acyltransferase was inhibited and choline phosphotransferase 1 (CEPT1) was activated after CTD intervention in mice and in HK-2 cells. CTD induces ATN, resulting in AKI, by activating GP metabolism and inhibiting SL metabolism in the renal cortex and medulla, LysoPC (16:0/0:0), LysoPC acyltransferase, and CEPT1 may be the therapeutic targets.